The influence of vergence facility on binocular eye movements during reading - Remo Poffa; Roland Joos (Bern Open Publishing, 2019)
Optometrists regularly use binocular measurements in patients with asthenopic complaints when performing close-up work. The focus of this work was therefore on the correlation of optometric parameters and objective fixation disparity (FD) measured by an eye tracker. In our investigation, 20 participants (6 male, 14 female) were subjected to a classical optometric procedure. Subsequently, these subjects read various sentences on a screen and eye movements were registered by using a RED500 eye tracker. The experiment was performed under two reading distance conditions. In order to be comparable with previous work, the present study was conducted under dark illumination conditions (J. A. Kirkby, Blythe, Drieghe, Benson, & Liversedge, 2013). FD values were deduced from objective eye tracking data during reading. Data analysis was done using linear mixed-effects models. FD was found to depend on vergence facility (t=3.3, p=0.004). Subjects with a low vergence facility showed more eso fixation disparity than subjects with a normal vergence facility. If studies of binocular coordination using eye tracking methods are performed under dark illumination conditions, vergence facility is an important parameter and should be accounted for. Neglecting this parameter may mask other important parameters. Vergence facility in context of reading difficulties may be important.